2021
DOI: 10.1002/chem.202004519
|View full text |Cite
|
Sign up to set email alerts
|

Design Platform for Sustainable Catalysis with Radicals: Electrochemical Activation of Cp2TiCl2 for Catalysis Unveiled

Abstract: The combination of synthesis, rotating ring‐disk electrode (RRDE) and cyclic voltammetry (CV) measurements, and computational investigations with the aid of DFT methods shows how a thiourea, a squaramide, and a bissulfonamide as additives affect the EqCr equilibrium of Cp2TiCl2. We have, for the first time, provided quantitative data for the EqCr equilibrium and have determined the stoichiometry of adduct formation of [Cp2Ti(III)Cl2]−, [Cp2Ti(III)Cl] and [Cp2Ti(IV)Cl2] and the additives. By studying the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Clearly, a non-linear effect is registered in our reaction. Since Ti( iii ) complexes are involved in associative or dissociative equilibria (in the case of Cp 2 TiCl 2 , the loss of the chloride ligand with the formation of the corresponding cationic complex), 26,39 the effective concentration of active titanium species can be hardly estimated. 40 Although it is difficult to attribute the suitable model to fit the data reported in Fig.…”
Section: Photophysical and Mechanistic Analysesmentioning
confidence: 99%
“…Clearly, a non-linear effect is registered in our reaction. Since Ti( iii ) complexes are involved in associative or dissociative equilibria (in the case of Cp 2 TiCl 2 , the loss of the chloride ligand with the formation of the corresponding cationic complex), 26,39 the effective concentration of active titanium species can be hardly estimated. 40 Although it is difficult to attribute the suitable model to fit the data reported in Fig.…”
Section: Photophysical and Mechanistic Analysesmentioning
confidence: 99%
“…This positive effect was observed for other anions (Br − , MsO − ) as well. Cyclic voltammetric, rotating ring‐disk electrode, and DFT studies revealed that these additives are not only suitable agents to cleave the Ti−Cl bond but also form supramolecular complexes with the various titanium species in solution by coordinating to the chloride ligands [52] . In case of the [Cp 2 TiCl 2 ]/[Cp 2 TiCl 2 ] − redox couple, this formation of a precomplex leads to a shift of the redox potential to slightly more positive values.…”
Section: Radical Arylationmentioning
confidence: 99%
“…Cyclic voltammetric, rotating ring-disk electrode, and DFT studies revealed that these additives are not only suitable agents to cleave the TiÀ Cl bond but also form supramolecular complexes with the various titanium species in solution by coordinating to the chloride ligands. [52] In case of the [Cp 2 TiCl 2 ]/ [Cp 2 TiCl 2 ] À redox couple, this formation of a precomplex leads to a shift of the redox potential to slightly more positive values. Our investigations suggested that this shift in reduction potential of the titanium(III) species may directly correlate with the observed binding affinity and abstraction power of the additive.…”
Section: Radical Arylationmentioning
confidence: 99%
“…Following the pioneering works on titanium­(III)-promoted and -catalyzed epoxide openings, -pinacol couplings, and -related reactions, our group has investigated catalytic-reductive Umpolung reactions in form of cross-couplings between Michael acceptors, ketones, imines, and nitriles. , More recently, we have reported titanium­(III)-catalyzed decyanations and desulfonylations . The catalytic systems of titanium­(III)-catalyzed reactions, however, are complex and additives such as amine or pyridine bases, amine hydrochlorides, and chlorotrimethylsilane have a strong effect on the reaction outcome. Moreover, ZnCl 2 or MnCl 2 , which are formed as byproducts of the turnover-enabling catalyst reduction with Zn or Mn, have an effect on the reactions as well. As a matter of fact, a strong influence of ZnCl 2 or MnCl 2 has been observed in earlier examples of epoxide opening/radical additions to Michael acceptors, and it was concluded that these salts either led to highly coordinated transition states or acted as Lewis acid cocatalysts (Scheme ).…”
Section: Introductionmentioning
confidence: 99%